Politics of Taxonomy in Postcolonial Indonesia Ethnic Traditions between Religionisation and Secularisation - Ramstedt, Martin 1962- (Historical social research, 2019)
The article discusses the politics of taxonomy that drive the entangled dynamics of religionisation and secularisation of ethnic traditions in postcolonial Indonesia, and the associated sociopolitical context. Defined in accordance with both emic notions of agamasasi (religionisation) and the concept of religion-making originally advanced by Arvind-Pal S. Mandair and Markus Dressler in 2011, “religionisation” relates to three interrelated processes that have had distinct ramifications in the different periods of postcolonial Indonesian history: (1) the way in which the Indonesian state has reified and institutionalised ‘religion’ as a monotheistic, revealed, and scriptural world religion; (2) the state-sanctioned positioning of ‘religion’ as distinct from local forms of spiritual belief, resulting in the desacralisation and secularisation of the latter; and (3) the way in which adherents of ethnic spiritualities have reframed and transformed their respective traditions in order to reflect the state-defined notion of ‘religion,’ and, in doing so, also accepted and strengthened the state discourse of development and modernity. The article also supports Nils Bubandt’s observation that the boundaries between the secular and the spiritual have always remained porous in Indonesian society as even so-called secular Indonesian politicians have tended to fall back on locally flavoured mystical or magical beliefs and practices in order to secure their political power.